ANALISIS PENGARUH RETURN HARGA KOMODITI DUNIA TERHADAP RETURN INDEKS HARGA SAHAM GABUNGAN DI INDONESIA PERIODE 2000 - 2010 - Reinandus Aditya Gunawan (Jurnal Manajemen, 2013)
In Indonesia the trend to invest in gold, silver, platinum and palladium is getting higher in the past 10 years. This study wants to find the relationship between the return of the commodity price with IHSG return as an indicator of Indonesian stocks. This relationship is sought to create a better alternative for investors. When the price of a commodity is up or down, will IHSG go up or down as well so investors can immediately shift their funds to commodity instruments or still hold shares listed in IHSG to avoid the risk of declining value of its investment. Results from this study indicate that global commodity return has a positive correlation with IHSG return. World commodity return also has an influence on IHSG return.